The Managementof of Channel Health Campaign and The Audience Attitude - Hasan Basri (Saburai International Journal of Social Sciences and Development, 2017)
Perspective recipients into basic research rests on the Theory of Planned Behavior of Ajzen and Martin Fishbein Icek (Ramdhani, 2007) which states that the intention of the behavior (behavior intention) is determined by the attitude of the behavior (attitude toward behavior) and subjective norm. This study proves that public attitudes can be influenced, but not a major factor in generating behavioral effects. That the theory underlying the study mentions the association of attitude change with behavior change, it can be said that the success of persuasion in campaign can be started by changing the attitude of the audience. The intended audiences are Posyandu cadres in which are subject to health campaign messages from the local government of Bandar Lampung City. In the population, quantitative research was conducted with path analysis of the communication channel variables used and the variable of attitude change in the audience. The findings of the communication channel used during the campaign contributed to the change of attitude. In this context, the most effective channel is the interpersonal communication between the communicator and the campaign audience. Can also be followed the development of communication channel management by presenting new media such as social media.